Three‐Dimensional Echocardiographic Evaluation of Mitral Apparatus during Preload Manipulation in Patients with Hypertrophic Cardiomyopathy. Issue 8 (20th November 2014) - Chung, Hyemoon; Yoon, Ji Hyun; Yoon, Young Won; Chung, Ji Young; Cha, Jung‐Joon; Kim, Jong‐Youn; Min, Pil‐Ki; Lee, Byoung‐Kwon; Hong, Bum‐Kee; Rim, Se‐Joong; Kwon, Hyuck Moon; Choi, Eui‐Young
<x xml:space="preserve">Abstract</x> Background The three‐dimensional (3D) dynamic change of mitral geometry during preload manipulation has not been fully investigated. We investigated how preload manipulation affected the mitral apparatus geometry in hypertrophic cardiomyopathy (HCM) patients using 3D echocardiography. Methods and Results Twenty five HCM patients, thirteen with obstructive HCM (HOCM) and twelve with nonobstructive HCM (HNCM), and six healthy controls were studied. Subjects underwent 3D echocardiography during rest, leg raising, the Valsalva maneuver, and the Valsalva maneuver after nitroglycerin intake (NTG‐Valsalva). Left ventricular outflow tract (LVOT) pressure gradients, mitral annular area, annular circumference, and the tenting volume of the mitral leaflets were measured. Standardized annular area significantly decreased during the NTG‐Valsalva maneuver in all 3 groups (▵2.23 mm2/m2 in control, P = 0.031; ▵0.46 mm2/m2 in HNCM, P = 0.012; ▵1.3 mm2/m2 in HOCM, P = 0.013). Standardized annular area decrease during the Valsalva maneuver alone was more prominent in HNCM patients (▵0.57 mm2/m2, P = 0.009) than HOCM patients (▵0.3 mm2/m2, P = 0.094). Standardized mitral tenting volume during the NTG‐Valsalva maneuver significantly decreased only in HOCM patients (▵1.18 mm3/m2, P = 0.046). Conclusion Decreased mitral annular area and changes in leaflets tenting volume during preload reduction might affect the development of LVOT obstruction. Our data suggest the importance of preserving the saddle‐shaped of the mitral annulus in management of HCM with LVOT obstruction.